2019
DOI: 10.1001/jamadermatol.2019.0052
|View full text |Cite
|
Sign up to set email alerts
|

Association of Leukemia Cutis With Survival in Acute Myeloid Leukemia

Abstract: IMPORTANCE Leukemia cutis (LC) is an important yet understudied extramedullary manifestation of leukemia. Previous reports have suggested poor prognosis for patients with LC, but these reports have largely consisted of descriptive studies with a limited number of patients. OBJECTIVES To identify patient factors associated with LC and characterize the association of LC with the course of acute myeloid leukemia (AML). DESIGN, SETTING, AND PARTICIPANTS This retrospective, matched-cohort study included 1683 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 32 publications
6
41
1
Order By: Relevance
“…Ganzel and colleagues, however, demonstrate that after adjusting for known prognostic risk factors such as older age, high white blood cell count, and cytogenetic risk factors, the presence of extramedullary disease did not have prognostic significance [28]. In contrast, Wang and co-authors found that patients with AML and LC as compared to those without LC had a hazard ratio of 2.06 for leukemia-specific death, after controlling for similar risk factors as Ganzel [29]. We did not find a statistical difference between the known prognostic risk factor-based predictions and the overall survival in our cohort.…”
Section: Figure 2 Kaplan-meier Curves Of Patients With Acute Myeloid Leukemia and Leukemia Cutis Classified Into Risk Categories By Europmentioning
confidence: 98%
See 1 more Smart Citation
“…Ganzel and colleagues, however, demonstrate that after adjusting for known prognostic risk factors such as older age, high white blood cell count, and cytogenetic risk factors, the presence of extramedullary disease did not have prognostic significance [28]. In contrast, Wang and co-authors found that patients with AML and LC as compared to those without LC had a hazard ratio of 2.06 for leukemia-specific death, after controlling for similar risk factors as Ganzel [29]. We did not find a statistical difference between the known prognostic risk factor-based predictions and the overall survival in our cohort.…”
Section: Figure 2 Kaplan-meier Curves Of Patients With Acute Myeloid Leukemia and Leukemia Cutis Classified Into Risk Categories By Europmentioning
confidence: 98%
“…Historically, LC has been believed to be associated with poor prognosis. However, modern assessment of patients with leukemia cutis in the context of genetic abnormalities and modern treatments has yielded mixed results [28,29].…”
Section: Dermatology Online Journal || Originalmentioning
confidence: 99%
“…Leukemia cutis (LC), also known as cutaneous myeloid sarcoma is not limited to neonatal period and remains common in infant leukemia. LC is commonly seen in FAB-4 and 5 AML [ 17 , 18 , 19 ]. Patients present with diffuse and papulonodular erythematous or violaceous skin lesions corresponding to leukemia infiltration into the epidermis, dermis or subcutaneous tissues [ 20 ].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In the French ELAM02 cohort, skin involvement was significatively more prevalent in infants occurring in 14.5% of children less than 2 years old compared to 2.6% of older children [ 1 , 19 ]. This presentation is associated with other extra-medullary organ involvement in AML and is negatively associated with prognosis [ 17 , 18 , 19 ]. One hypothesis is that chemotherapy sufficient to induce remission in bone marrow may not be sufficient to penetrate the skin, thus leading to a greater incidence of relapse in those patients.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Cutaneous involvement usually occurs in the setting of bone marrow, internal organ and peripheral blood involvement, portending a poor outcome. Therefore, it is of paramount importance to screen all patients with specific cutaneous lesions of leukaemia to exclude simultaneous internal organ disease 17,18 …”
Section: Leukaemiamentioning
confidence: 99%